2022
DOI: 10.11144/javeriana.rgps21.fvpc
|View full text |Cite
|
Sign up to set email alerts
|

Fin de vida en pacientes con cáncer no curable. Percepciones de los pacientes sobre el sistema de salud

Abstract: Objetivo: Identificar y analizar experiencias y opiniones que pacientes oncológicos sin opción curativa tienen respecto al sistema de salud en torno a sus cuidados paliativos y deseos de final de vida. Métodos: Estudio cualitativo con perspectiva crítico-constructivista. Se realizaron 22 entrevistas en profundidad a pacientes entre 28 y 78 años con algunos de los cánceres más frecuentes (mama, cuello uterino, colon, estómago, entre otros, con una expectativa de vida entre seis y doce meses) atendidos en … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Tramadol, dihydrocodeine and codeine are the most widely available options. Vries et al, (2022) has described that tramadol is widely used in palliative care, although data on its use are limited and adverse effects can be serious. In addition, Merino et al, (2019), considers tramadol to have a potential role in step 2 of the analgesic ladder.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tramadol, dihydrocodeine and codeine are the most widely available options. Vries et al, (2022) has described that tramadol is widely used in palliative care, although data on its use are limited and adverse effects can be serious. In addition, Merino et al, (2019), considers tramadol to have a potential role in step 2 of the analgesic ladder.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the fatigue-related symptoms, in the study of Vries et al, (2022) showed that nurses were trained to guide patients to help family and friends, and also to help patients gain more social support. Thus, Merino et al, (2019) They add that these measures alleviate patients' anxiety, depression and relieve their emotional fatigue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation